Associations between the parent–child relationship and adolescent self‐worth: a genetically informed study of twin parents and their adolescent children. (18th July 2016) - McAdams, Tom A.; Rijsdijk, Fruhling V.; Narusyte, Jurgita; Ganiban, Jody M.; Reiss, David; Spotts, Erica; Neiderhiser, Jenae M.; Lichtenstein, Paul; Eley, Thalia C.
Abstract : Background: Low self‐worth during adolescence predicts a range of emotional and behavioural problems. As such, identifying potential sources of influence on self‐worth is important. Aspects of the parent–child relationship are often associated with adolescent self‐worth but to date it is unclear whether such associations may be attributable to familial confounding (e.g. genetic relatedness). We set out to clarify the nature of relationships between parental expressed affection and adolescent self‐worth, and parent–child closeness and adolescent self‐worth. Methods: We used data from the Twin and Offspring Study in Sweden, a children‐of‐twins sample comprising 909 adult twin pairs with adolescent children. Using these data we were able to apply structural equation models with which we could examine whether associations remained after accounting for genetic transmission. Results: Results demonstrated that parent–child closeness and parental‐expressed affection were both phenotypically associated with adolescent self‐worth. Associations could not be attributed to genetic relatedness between parent and child. Conclusions: Parent–child closeness and parental affection are associated with adolescent self‐worth above and beyond effects attributable to genetic relatedness. Data were cross‐sectional, so the direction of effects cannot be confirmed but findings support the notion that positive parent–child relationships increase adolescent self‐worth.